STRATEGIES TO INCREASE THE EFFECTIVENESS OF ABILITIES FASHARKAN MENTIGI OF TANJUNG UBAN TO SUPPORT THE STATE DEFENSE - As'ad Aris Mustofa; Avando Bastari; Eko Krisdiono (Indonesian Naval Technology College STTAL, 2021)
The maintenance and repair facility is one of the organizations within the Indonesian Navy that has the task of carrying out the maintenance and repair of KRI. In carrying out increasingly complex tasks, and the development of marine lift technology, maintenance and repair facilities require technological equipment and professional personnel in their fields. The purpose of this research is to determine alternative strategies to increase the effectiveness of the ability of Fasharkan Mentigi Tanjung Gray. This research uses the integration of SWOT analysis which is used to formulate and provide alternatives in the development strategy of the Mentigi Tanjung uban Fasharkan. Based on the results of the SWOT matrix analysis, in order to increase the effectiveness of the ability of the Tanjung Uban Mentigi Fasharkan to support the main duties of the Indonesian Navy, according to the SWOT method shows that the effectiveness strategy of fasharkan's ability lies in quadrant II with coordinates (0.38; 0.32) which indicates the SO strategy, namely the ability of the Mentigi Tanjung Uban Fasharkan to use optimal strength by taking advantage of existing opportunities, with alternative strategies The first is (1) the readiness of fasharkan to increase the effectiveness of the Mentigi Tanjung Uban Fasharkan capability which is supported by the Indonesian Navy policy and the Fasharkan operational strategy; and (2) the readiness of personnel supported by the development and training of personnel capabilities namely the ability of Fasharkan Mentigi Tanjung Uban to use optimal strength by taking advantage of existing opportunities, with the first alternative strategy being (1) Fasharkan readiness to increase the effectiveness of the Tanjung Uban Mentigi Fasharkan ability which is supported by the Indonesian Navy policy and Fasharkan's operational strategy; and (2) the readiness of personnel supported by the development and training of personnel capabilities namely the ability of Fasharkan Mentigi Tanjung Uban to use optimal strength by taking advantage of existing opportunities, with the first alternative strategy being (1) Fasharkan readiness to increase the effectiveness of the Tanjung Uban Mentigi Fasharkan ability which is supported by the Indonesian Navy policy and Fasharkan's operational strategy; and (2) the readiness of personnel supported by the development and training of personnel capabilities Keywords : Fasharkan Mentigi Tanjung Pinang, SWOT